Limbo [videorecording (Blu-Ray)] - Baker, Simon, 1986-; Collins, Rob, 1979-; Wanganeen, Natasha; Hope, Nicholas, 1958- (Brainstorm Media, 2025)
Jaded police detective Travis arrives in the remote Australian Outback town of Limbo to investigate the cold case murder of a local Indigenous girl 20 years ago. As truths about the crime begin to unfold, Travis gains new insight into the unsolved case from the victim's fractured family, the surviving witnesses, and the reclusive brother of the chief suspect. Shot in starkly beautiful black and white, Limbo is a penetrating modern noir and a poignant, intimate journey into the complexities of loss.